Effectiveness of A Combination of Kitolod Leaves (Laurentia longiflora), Papaya Leaves (Carica papaya), and Lemongrass (Cymbopogon citratus) as Candidates for Biocides on Bactrocera Pests in Citrus sinensis Plants - Wakhidya, Savira Amilda; Rohman, Fatchur; Setiowati, Frida Kunti; Abdul Razak, Sarah (Jurnal Riset Biologi dan Aplikasinya, 2024)
Bactrocera is a pest that is detrimental to citrus farming. Bactrocera attacks cause developmental disorders in citrus fruit, including changes in fruit color (black spots appear from Bactrocera infection) and premature rot. Bactrocera also has a symbiotic relationship with Liberibacter asiaticus which causes Citrus Vein Phloem Degeneration (CVPD) disease which attacks phloem tissue in citrus plants. Bactrocera pest control was carried out by combining plants that have the potential to be used as biocides, namely kitolod, papaya, and lemongrass plants. This combination was used to switch the habits of fruit farmers who previously used synthetic pesticides to control pests.   Natural biocides are expected to have the same effectiveness as synthetic pesticides, but leave no residue on cultivated plants. A combination biocide from the three plants was made using the maceration method to obtain an infusion from each plant. Before being tested on Citrus plantations, an assay was carried out using an olfactometer to determine the effectiveness of the biocides. The research revealed that the combination of these three plants has the potential to be used as a natural biocide without leaving residueand causing damage or other developmental disorders to citrus plants.